Sequência didática em uma abordagem transversal como estratégia para o estudo do som no ensino fundamental - Santos, Ivan Viana dos (2021)
This paper presents the report of development and application of a didactic sequence for study of sound in a 9th grade class in a elementary school. To trigger the didactic sequence, a problem-situation was formulated based on the idea that sound can sometimes cause noise pollution, generating a conflicting situation in students' experiential reality. When we think of sound, we conclude that we are, in fact, immersed in a world of sound waves what can raise countless questions. Through this problem situation the students were encouraged to investigate this chosen theme in order to know the impact caused by sound on our lives and to evaluate the risks that some sound sources may cause to our health and the life of other living beings. To apply the didactic sequence, three main actions were developed: 1) A presentation of the problem-situation to the students, 2) Investigation and generalization of conclusions drawn from research sources, and 3) An oral presentation of research reports. During the execution of these tasks, students had the opportunity to develop important competences and skills for understanding the process of science construction and for learning physical concepts, among which we highlight teamwork, the ability to recognize sources of information. relevant to the investigation of a problem, the ability to mobilize resources and people and to listen and give opinions. The results of this work made it possible to improve the developed didactic sequence that is presented in the Appendix in the form of an educational product to assist elementary schools science teachers in approaching the concept of sound to their students.